Study of Placement and Design of Thermoelectric Generator at Outdoor Air Conditioner Harvesting Energy for Closed-Circuit Television (CCTV) Application - Abd Rahim, Muhammad Haikal; Nor Aira Zambri; Farahiyah Mustafa (Progress in Engineering Application and Technology, 2025)
In today’s world, harnessing energy through recycling provides a viable option to promote a greener environment. Air conditioning systems are among the largest energy consumers in the world, mainly used to control the internal temperature of buildings. In Malaysia, split unit air conditioning systems are popular for small spaces. However, the heat released by the outdoor unit is often wasted. This issue can be addressed by utilizing a Peltier device as a thermoelectric generator module (TEG). The purpose of this project is to design a thermoelectric generator (TEG) capable of capturing wasted heat from an outdoor unit and converting it into electricity, while determining the optimal location for maximum electricity generation. The TEG uses a Peltier device, which is sandwiched between copper plates measuring 40 mm x 40 mm x 2 mm. One side of the copper plate is positioned in a high-heat area, while the other side is attached to a heat sink with a lower temperature to facilitate efficient heat transfer. Five Peltier modules have been arranged in series or in parallel between the iron plates to differentiate output such as voltage and current. Two locations placed differently are monitored based on the temperature difference (ΔT) between the compressor and the condenser, also between compressor tank and condenser copper pipe. The highest ΔT was recorded in between heat tank and condenser copper pipe, alongside simultaneous voltage output measurements for each Peltier module. A maximum voltage of 1.0 V is generated from the split unit air conditioner after 60 minutes of operation, with a ΔT of about 35-40 °C. The application of TEG technology for heat recovery offers a promising solution for converting waste heat into electricity, providing a valuable alternative for meeting small-scale household energy needs. To enhance its performance, the TEG is integrated with a power management system that ensures a stable and reliable power output. The generated power is then used to power CCTV appliances, such as cameras and monitors, reducing the need for external power sources. The results will also provide valuable insights into the potential of thermoelectric technology for energy harvesting and the feasibility of integrating it with existing infrastructure.